2010
DOI: 10.1021/ed100166g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoprisms with Variable Size and Investigation of Their Optical Properties: A First-Year Undergraduate Experiment Exploring Plasmonic Nanoparticles

Abstract: A robust and reasonably simple experiment is described that introduces students to the visualization of nanoscale properties and is intended for a first-year laboratory. Silver nanoprisms (NPs) that display different colors due to variation of their plasmonic absorption with respect to size are prepared. Control over the size of the silver nanoprisms is achieved using a novel approach, where bromide is added to the reaction as a size-determining agent, and silver ions are reduced by borohydride in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 20 publications
5
111
0
9
Order By: Relevance
“…Especially, anisotropic gold nanostructures are an interesting class of structures due to their unique optical, electrical, magnetic and catalytic properties that directly correlate with their shape and size [3][4][5][6]. They have been synthesized using a variety of methods, including chemical reduction and seed-mediated growth methods in aqueous phase [7].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, anisotropic gold nanostructures are an interesting class of structures due to their unique optical, electrical, magnetic and catalytic properties that directly correlate with their shape and size [3][4][5][6]. They have been synthesized using a variety of methods, including chemical reduction and seed-mediated growth methods in aqueous phase [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is also need for more information on NPs toxicity. Recently has been demonstrated that physiological barriers such as pulmonary and gastro-intestinal tract are affected [1,2].The main objective of this work is to use functionalized metal NPs, as emissive agent markers, assess their internalization in cells and evaluate toxicity to cells.Using the emissive two probes synthesized in a one-pot reaction using fluoresceine as chromophore, several gold (Au), round shape, and silver (Ag) NPs (round and triangular shapes) were functionalized in organic media and water by Brust [3] and Turkevish [4] methodology, using tetraoctylammonium bromide (TOABr) as a common stabilizer and sodium borohydride as reducing agent. All has been characterized by UV-vis and emission spectroscopy, transmission electron microscopy (TEM) (Figure 1), and Light scattering.…”
mentioning
confidence: 99%
“…Additionally, there is also need for more information on NPs toxicity. Recently has been demonstrated that physiological barriers such as pulmonary and gastro-intestinal tract are affected [1,2].…”
mentioning
confidence: 99%
“…A nanociência e o resultado dela, a nanotecnologia, já são temas muito explorados e discutidos em vários cursos de graduação em outros países. [8][9][10] As aulas experimentais de Química Inorgânica ou Físico-Química são, portanto, um caminho bastante adequado para a introdução dos conceitos de nanociência para alunos de graduação do último ano de curso. Isso se deve, não apenas pelo interesse tecnológico em torno do assunto, mas também pelo fato de que um experimento simples como esse que será apresentado aqui resgata e coloca em prática conceitos básicos de Química, como teorias de ligação metálica, estrutura atômica, reações de oxidação-redução e espectroscopia, ao mesmo tempo em que introduz novos conceitos, muitos deles não vistos em sala de aula, como o efeito de confinamento quântico e a ressonância de plasmons de superfície.…”
unclassified